Características das ilhas de calor em cidades de porte médio: exemplos de Presidente Prudente (Brasil) e Rennes (França) - Margarete Cristiane de Costa Trindade Amorim; Vincent Dubreuil; Hervé Quenol; João Lima Sant’Ana Neto (Confins)
This paper aims to analyze and compare thermal characteristics of urban climate of two middle size cities: Rennes (France) and Presidente Prudente (Brazil), by registering air temperature (network pointes and mobile transect) and surface data obtained by using Landsat7 satellite thermal images. Results show that temperature grows faster in Rennes than Presidente Prudente and urban heat island generation (UHI) by different cities urbanization processes.